Right Node Raising and Gapping : Interface conditions on prosodic deletion. - Hartmann, Katharina (John Benjamins Pub. Co., 2001)
This book investigates two elliptical coordinations in German, Right Node Raising and Gapping. Ellipsis in both constructions is claimed to be the result of a phonological process which is conditioned by prosodic and focus semantic constraints. It is convincingly argued that Right Node Raising cannot involve raising to the right periphery: The alleged movement freely violates any of the well-known restrictions on syntactic movement and it does not alter the scope relations within the coordination. Gapping in contrast is more sensitive to syntactic conditions in that its remnants must be major.